Education, social factors, and health beliefs in health and health care services - Kronenfeld, Jennie J. (Research in the sociology of health care, 2015)
This volume provides a unique sociological focus on education, social factors and health beliefs in health and health care, including a review of the literature to date. Beliefs and health beliefs are considered, including one study evaluating cross-national differences in public beliefs about the causes of health and the role of these beliefs in shaping attitudes to health policy. Another study focuses on the complexity and variation of health care system distrust across neighborhoods in one US city. The topic of education is addressed, including a focus on the importance of identification and intervention in low health literacy. Mental health issues are considered in the context of help-seeking, connections, transitions and utilization of care among adolescents. Social factors are reflected upon including race and ethnicity, literacy and socioeconomic status. Coverage also includes special and traditionally less visible populations, including the health of prisoners and carers of people with autism."